Auxinic herbicides, mechanisms of action, and weed resistance: A look into recent plant science advances (Scientia Agricola, 2015)
Auxin governs dynamic cellular processes involved at several stages of plant growth and development. In this review, we discuss the mechanisms employed by auxin in light of recent scientific advances, with a focus on synthetic auxins as herbicides and synthetic auxin resistance mechanisms. Two auxin receptors were reported. The plasma membrane receptor ABP1 (Auxin Binding Protein 1) alters the structure and arrangement of actin filaments and microtubules, leading to plant epinasty and reducing peroxisomes and mitochondria mobility in the cell environment. The second auxin receptor is the gene transcription pathway regulated by the SCFTir/AFB ubiquitination complex, which destroys transcription repressor proteins that interrupt Auxin Response Factor (ARF) activation. As a result mRNA related with Abscisic Acid (ABA) and ethylene are transcribed, producing high quantities of theses hormones. Their associated action leads to high production of Reactive Oxygen Species (ROS), leading to tissue and plant death. Recently, another ubiquitination pathway which is described as a new auxin signaling route is the F-box protein S-Phase Kinase-Associated Protein 2A (SKP2A). It is active in cell division regulation and there is evidence that auxin herbicides can deregulate the SKP2A pathway, which leads to severe defects in plant development. In this discussion, we propose that SFCSKP2A auxin binding site alteration could be a new auxinic herbicide resistance mechanism, a concept which may contribute to the current progress in plant biology in its quest to clarify the many questions that still surround auxin herbicide mechanisms of action and the mechanisms of weed resistance.